2015
DOI: 10.1517/13543784.2015.1051220
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of cancer stem cells by inhibitors of DNA and histone methylation

Abstract: Agents that target EZH2 warrant Phase I trials. Due to its positive pharmacodynamics, DZNep merits a high priority for clinical investigation. Agents that show positive results in Phase I studies should be advanced to clinical trials for use in combination with 5-aza-2'-deoxycytidine due to the interesting potential of this epigenetic therapy to target CSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 89 publications
0
29
0
1
Order By: Relevance
“…25 Through H3K27me3, EZH2 suppresses differentiation of mesenchymal stem cells and potential cancer stem cells. 26 Point mutations that increase the catalytic activity of EZH2 promote cell transformation in subsets of B-cell neoplasms, thus making EZH2 a compelling target in this genetically defined patient population. 27 EZH2 inhibitors were shown to have strong antitumor effects against human B-cell lymphoma xenograft models.…”
Section: Discussionmentioning
confidence: 99%
“…25 Through H3K27me3, EZH2 suppresses differentiation of mesenchymal stem cells and potential cancer stem cells. 26 Point mutations that increase the catalytic activity of EZH2 promote cell transformation in subsets of B-cell neoplasms, thus making EZH2 a compelling target in this genetically defined patient population. 27 EZH2 inhibitors were shown to have strong antitumor effects against human B-cell lymphoma xenograft models.…”
Section: Discussionmentioning
confidence: 99%
“…The upstream regulatory mechanisms of HOTAIR expression in OA also need to be determined, which may involve interactions with other lncRNAs (54) or mechanoresponsive pathways (55). Furthermore, histone methylation is known to be affected by inhibitors of DNA methylation, such as 5-Aza-2'-deoxycytidine which is used as an anti-cancer drug (56,57), and it would be interesting to investigate the effects of applying such compounds on HOTAIR signalling in OA. These additional ndings building on the results of this study will con rm our proposed mechanism, and potentially improve the accuracy of predictive models for the pathogenesis of cartilage damage in OA (58).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, preclinical studies have shown that ( 1 ) in combination with 3-deazaneplanocin-A (DZNep) ( 8 ) produce a synergistic reactivation of CDKN1A (Cyclin-dependent kinase inhibitor 1A), CDKN1B and FBXO32 (F-Box Protein 32) genes [32,33]. In fact, ( 8 ) is an inhibitor of S -adenosyl-L-homocysteine (SAH) hydrolase, an enzyme involved in the degradation of SAH (or AdoHcy), the product of the methylation reaction and a natural inhibitor of HMTs and other enzymes.…”
Section: Inhibition Of Dna Methylationmentioning
confidence: 99%
“…As evoked above, the combination of DNMTi 1 and the SAH hydrolase inhibitor ( 8 ) represents this emerging approach [33]. Furthermore, keeping in mind that SAM is the cofactor of both DNMT and HMTs, dual inhibitors, i.e., agents with a double effect, might also represent an interesting anticancer approach [84].…”
Section: Inhibition Of Dna Methylation: Other Approachesmentioning
confidence: 99%